From enjoyment to physical activity or from physical activity to enjoyment? Longitudinal associations in parent–child dyads. Issue 10 (3rd October 2018) - Kruk, Magdalena; Zarychta, Karolina; Horodyska, Karolina; Boberska, Monika; Scholz, Urte; Radtke, Theda; Luszczynska, Aleksandra
Abstract: Background: This longitudinal dyadic study used cross-lagged analyses to examine reciprocal patterns of associations between physical activity (PA) enjoyment and moderate-to-vigorous PA (MVPA) among children and their parents. Methods: At Time 1 (T1) 879 parent–child dyads provided their data. The follow-up (Time 2, T2) took place 7–8-months later. MVPA and PA enjoyment scales were filled out separately by parents and children at T1 and T2. Findings : Child PA enjoyment (T1) predicted a higher level of child MVPA (T2), parental PA enjoyment (T1) explained a higher level of parental MVPA (T2), and parental MVPA (T1) predicted a higher level of parental PA enjoyment (T2). Furthermore, child PA enjoyment (T1) predicted a higher level of parental PA enjoyment (T2). Conclusions: Child PA enjoyment was the key variable predicting child and parental outcomes. In particular, it explained child MVPA, but also PA enjoyment among parents.